Delayed Management of Pediatric Testicular Torsion with Absence of Severe Pain : An Evidance-Based Case Report - Kartika, Pramudita Angga; Sholihin, Riza Mazidu (Universitas Negeri Gorontalo, 2023)
Testicular torsion is a surgical emergency. To protect the affected gonad, early diagnosis and surgical therapy are essential. The pediatrician's difficulty in communicating his complaints is one of the potential patient-specific causes for a delayed diagnosis related to any of these symptoms. We describe a case of unilateral testicular torsion in a 13-year-old child who had complained of swelling but hadn't experienced intense scrotal discomfort in six days. His right testicle was completely shattered. When the right testicle was discovered to have a 360-degree torsion and to be detorted but not viable in the operating room, it had an orchidectomy, and the left testis underwent an orchidopexy. Three internet databases—PubMed, Google Scholar, and Science Direct—were used to search the literature. An English journal that discusses pediatric testicular torsion has inclusion criteria. There is insufficient research on testicular torsion that manifests with painless symptoms. Treatment could be postponed if this phenomenon isn't considered appropriately.Keywords : Delayed management, painless, pediatrics, testicular torsion